Depiction of a male figure in a niche - Temples of India Project Team (Jio Institute, 2024)
In a niche on the southern wall, of the garbhagriha (sanctum sanctorum) of the Kaner-ki-Putli Temple, a male figure is depicted. Unfortunately, the figure is damaged, with the head entirely missing. Both upper arms are broken, while the figure holds a kamandalu (water carrier or pot) in the left hand and makes a varadahasta (boon-giving gesture) with the right hand. At the base of the niche, a broken ram-like animal with horns is visible. Based on the vahana (mount), attributes, and gestures, this figure can be recognized as Agni (one of the deities of cardinal directions). Adjacent to Agni, there is a male figure that stands out from the others. This figure features curly, raised hair and a beard, but unfortunately, the face has been eroded. The upper body is bare and adorned with jewellery, while the lower body is covered by a distinctive triangular loin cloth. An antaravastra (inner garment) is visible beneath the loin cloth. The figure is draped with a scarf wrapped around the arms, and although the broken object held in his two hands is now incomplete, the visible middle part resembles a stick. Notably, this figure is unique because of the distinctive dressing style and footwear, suggesting him to be a foreigner.